2018
DOI: 10.1097/cad.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of anaplastic lymphoma kinase promotes apoptosis and suppresses proliferation in human hepatocellular carcinoma

Abstract: Our study was to examine the roles of crizotinib and ceritinib in hepatocellular carcinoma (HCC) cells and explore the possible mechanisms. MTT assay was employed to examine the proliferation of five HCC cell lines treated with various concentrations of crizotinib or ceritinib. HepG2 and HCCLM3 cells were incubated with 2 nmol/l ceritinib for 1 week, followed by crystal violet staining and cell counting. Protein amounts of t-ALK, p-ALK, t-AKT, p-AKT, t-ERK, p-ERK, Mcl-1, survivin, and XIAP in HepG2 cells under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The positive effect of ALK inhibition in HCC in vitro was recently demonstrated by Yu et al . Two approved inhibitors crizotinib and ceritinib suppressed the proliferation of HCC cell lines and inhibited the ALK phosphorylation; moreover, ceritinib treatment induced cell apoptosis [ 19 ]. Therefore, it seems that in HCC ALK inhibition is beneficial, even though the mechanism of ALK activation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive effect of ALK inhibition in HCC in vitro was recently demonstrated by Yu et al . Two approved inhibitors crizotinib and ceritinib suppressed the proliferation of HCC cell lines and inhibited the ALK phosphorylation; moreover, ceritinib treatment induced cell apoptosis [ 19 ]. Therefore, it seems that in HCC ALK inhibition is beneficial, even though the mechanism of ALK activation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be unlikely that the observed ALK phosphorylation in this study would have been due to antibody cross reaction with EGFR. Furthermore, antibody Tyr1604 has been utilized frequently to detect p-ALK in multiple malignancies including HCC, non-small cell lung carcinoma as well as neuroblastoma [ 19 , 24 26 ]. Thus, we suggest that our observation of ALK expression and phosphorylation in MCC tumor samples is genuine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, crizotinib (CRIZO) increases ROS in HL-7702 cells to promote pyroptosis and inhibit HCC [ 159 ]. Furthermore, CRIZO induces apoptosis and suppresses the proliferation of HCC cells by inhibiting the phosphorylation of the anaplastic lymphoma kinase (ALK), Akt, and ERK [ 160 ]. In addition, Cannabidiol (CBD), a cannabis sativa constituent, may induce pyroptosis via caspase-3/GSDME pathway to inhibit the growth of HCC cells in vivo and in vitro [ 161 ].…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…Furthermore, to suggest potential new strategies for the treatment of HCC, we conducted a drug correlation analysis between signature genes and drugs and then found that the drug sensitivity of oxaliplatin and LDK-378 was negatively correlated with ITGAV expression. Oxaliplatin is a standard treatment option for HCC [ 41 ], and LDK-378, a prospective inhibitor of anaplastic lymphoma kinase [ 68 ], was shown to promote apoptosis and suppress the proliferation of HCC cells [ 69 ]. The 10 anti-HCC drugs screened in the GDSC database, including embelin, bleomycin, epothilone B, midostaurin, CGP.082996, doxorubicin, MK.2206, GSK269962A, PF.562271, and gemcitabine, had lower IC50 in the high-risk group, demonstrating their potential superior performance against cancer in the high-risk group and offering the possibility of reducing the risk of progression in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%